The Comparative Analysis of Microplastic Contamination in Kembung (Rastrelliger sp) and Kurisi Fish (Nemipterus nemurus) from Coastal Waters of Mangindara, Indonesia - Alfina Baharuddin; Yuliati Yuliati; Suharni Suharni; Ardin Ardin (PT.Mantaya Idea Batara, 2026)
Background: Microplastics are a major component of marine debris, andtheir accumulation in aquatic environments can disrupt marine food chains,particularly in fish. Mangindara Village, South Galesong District, TakalarRegency, is a coastal area currently experiencing severe environmentalpollution, especially from plastic waste and household effluents. This condition raises serious concern, as plastic debris can degrade into microplastics that are not visible to the naked eye, enter marine organisms such as fish, and ultimately pose risks to human health. Methods: This study employed an observational design with a descriptive approach and laboratory analysis to examine the presence, types, and abundance of microplastics in Fish kembung (Rastrelliger sp.) and kurisi (Nemipterus nemurus) collected from the waters of Mangindara Village. The study population consisted of fish kembung and kurisi fish captured in the study area. Samples were selected using random sampling, with three individuals from each species analyzed. Results: The results showed that all examined fish samples contained microplastics. The average microplastic concentration in fish kembung was 0.061 g, whereas kurisi fish exhibited a higher average concentration of 0.085 g. The identified microplastics were predominantly line-shaped and appeared in blue, black, and red colors. Conclusion: These findings indicate widespread microplastic contamination in coastal fish species consumed by local communities. Therefore, reducing single-use plastic use and improving proper waste management practices are strongly recommended.